Now available: ORNAC Guidelines for Perioperative Practice in Canada – 17th Edition! - ORNAC (Operating Room Nurses Association of Canada Journal, 2025)
ORNAC is proud to announce that the 17th edition of the Guidelines for Perioperative Practice in Canada (formerly the ORNAC Standards, Guidelines, and Position Statements for Registered Nurses) is now available for purchase!